Eksplorasi Cacing Sonari sebagai Kearifan Lokal - Wahidi Wahidi; Lenny Mulyani; Dhinar Yatmiarti (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to explore the habitat of sonari worms as local wisdom at SMA Negeri 1 Ciwidey. This research is a best practice using observation methods including the stages of determining location, sampling, measuring soil physical and chemical properties, worm sampling, and measuring morphometry. The results showed that this best practice activity can be used as a reference in learning biology based on local wisdom. Sonari worms are believed to be a very powerful anti-fever drug by residents around the Mount Halimun-Salak and Gede Pangrango areas. The use of Sonari worms as a traditional medicine ingredient on a commercial scale will certainly threaten the preservation of the type and potentially cause environmental damage. Therefore, the habitat of Sonari worms needs to be maintained and preserved so that it does not become extinct and become local wisdom.